METHODOLOGICAL PRINCIPLES OF STRUCTURING CONTENTS OF SUBJECTS OF THE HUMANITARIAN CYCLE IN THE PROCESS OF PROFESSIONAL TRAINING OF STUDENTS OF PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
This article determines methodological basis of Art courses contents in the process of teaching students in pedagogical higher education establishments.
Keywords: art courses contents; education process humanization; education humanitarization; education professional efficiency